1997
DOI: 10.1523/jneurosci.17-16-06236.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Animal Model of Human Neocortical Heterotopia Associated with Seizures

Abstract: Malformations of the human neocortex are commonly associated with developmental delays, mental retardation, and epilepsy. This study describes a novel neurologically mutant rat exhibiting a forebrain anomaly resembling the human neuronal migration disorder of double cortex. This mutant displays a telencephalic internal structural heterotopia (tish) that is inherited in an autosomal recessive manner. The bilateral heterotopia is prominent below the frontal and parietal neocortices but is rarely observed in temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 31 publications
8
100
0
1
Order By: Relevance
“…As in irradiated rats, studies in MAM-treated rats have documented long-range connections between heterotopic gray matter and normal cortical and subcortical targets Yurkewicz et al 1984). Tish rat is a spontaneous mutant that has unprovoked epileptic seizures and a large, tubular mass of heterotopic cortex that lies in the white matter beneath the frontoparietal cortex of each cerebral hemisphere (Lee et al 1997). Heterotopic neurons in this model also show reciprocal connections with cortical and subcortical brain structures (Schottler et al 1998).…”
Section: Discussionmentioning
confidence: 97%
“…As in irradiated rats, studies in MAM-treated rats have documented long-range connections between heterotopic gray matter and normal cortical and subcortical targets Yurkewicz et al 1984). Tish rat is a spontaneous mutant that has unprovoked epileptic seizures and a large, tubular mass of heterotopic cortex that lies in the white matter beneath the frontoparietal cortex of each cerebral hemisphere (Lee et al 1997). Heterotopic neurons in this model also show reciprocal connections with cortical and subcortical brain structures (Schottler et al 1998).…”
Section: Discussionmentioning
confidence: 97%
“…2B) extending dorsally from the frontal to the dorsoparietal (apparently unaffected) neocortex (26). The heterotopia is present bilaterally, contains neurons with neocortical appearance, and displays near-normal connections with subcortical targets (27).…”
Section: The Tish Mutantmentioning
confidence: 99%
“…A particularly useful animal for this purpose is the seizure-prone genetic mutant termed the telencephalic internal structural heterotopia (tish) rat. An autosomal recessive mutation in the tish rat results in the development of bilateral subcortical band heterotopia reminiscent of those found in the human seizure disorder of subcortical band heterotopia or double cortex (Lee et al, 1997). The heterotopia consist of misplaced cortical neurons and glia that retain several basic features of normal neocortex, including topographic connectivity with subcortical targets (Lee et al, 1997Schottler et al, 1998Schottler et al, , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterotopic neurons fail to orient and laminate as in typical neocortex. Overlying the heterotopia is an area of the neocortex termed "normotopic cortex" that is thinner than normal neocortex but maintains proper orientation and lamination of its primary neurons (Lee et al, 1997(Lee et al, , 1999Schottler et al, 1998Schottler et al, , 2001. Electrophysiological studies have demonstrated that spontaneous seizure activity occurs in both normotopic and heterotopic areas of the adult tish neocortex, but that the normotopic area is more prone to develop aberrant discharge activity (Chen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation